2007
DOI: 10.1038/sj.ki.5002406
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of vitamin D receptor activators on vascular calcification in uremic rats

Abstract: Vascular calcification is associated with cardiovascular disease, the most common cause of death in chronic kidney disease (CKD). Patients with CKD are treated with vitamin D receptor activators (VDRAs); therefore, we determined if this treatment affects vascular calcification. Uremic rats were given vehicle, calcitriol, paricalcitol, or doxercalciferol three times a week for 1 month. Calcitriol significantly increased the serum calcium-phosphate product and aortic calcium content. Paricalcitol had no effect b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
156
1
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(172 citation statements)
references
References 40 publications
8
156
1
7
Order By: Relevance
“…10,12,15 The actions of the VDR activators on aortic calcification reported here are not in disagreement with these reports, because when we used a dosage of paricalcitol (paricalcitol 400 ng/kg) equivalent to the VDR activator dosages used in the previous reports; we also observed stimulation of aortic Ca content (Figure 1). The stimulation of vascular Ca content in the group that was treated with 400 ng/kg paricalcitol was due to increased deposition of vascular Ca in the atherosclerotic plaque.…”
Section: Resultssupporting
confidence: 37%
“…10,12,15 The actions of the VDR activators on aortic calcification reported here are not in disagreement with these reports, because when we used a dosage of paricalcitol (paricalcitol 400 ng/kg) equivalent to the VDR activator dosages used in the previous reports; we also observed stimulation of aortic Ca content (Figure 1). The stimulation of vascular Ca content in the group that was treated with 400 ng/kg paricalcitol was due to increased deposition of vascular Ca in the atherosclerotic plaque.…”
Section: Resultssupporting
confidence: 37%
“…Moreover, while in vitro studies suggested a protective role for vitamin D in ameliorating damaged endothelium,12, 13 experimental in vivo CKD studies have primarily focused on the prevention of vascular calcification of the medial layer and heart failure9, 14, 15 but paid little attention to structural endothelial damage. A small number of prior studies have suggested benefits of the active vitamin D analogue paricalcitol on endothelial stability in animal models of CKD16, 17 and even in patients 18, 19.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of which VDRA to use should be based on clinically exposed differences in efficacy and safety. New preclinical studies indicate that calcitriol and doxercalciferol but not paricalcitol stimulate aortic expression of cbfa1/runx2 and osteocalcin, in addition to promoting marked aortic calcium accumulation (27). This suggests a potential protective effect for paricalcitol for not stimulating aortic vascular smooth muscle cells to undergo a transition to the osteoblast phenotype under conditions of hyperphosphatemia (28).…”
Section: Vdra Therapymentioning
confidence: 97%